Inhibitory Effect on -Glucosidase by Traditional Thai Medicinal Plants - Rungprom*, Wimolpun (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
a -glucosidase inhibitors are utilized in the treatment of type II diabetes mellitus (DM). The inhibition of intestinal a -glucosidase would delay the digestion and absorption of carbohydrates and consequently suppress postprandial hyperglycemia. Thai medicinal plants are widely used in the treatment of diabetes mellitus. An attempt to verify their Inhibitory effect on a-glucosidase from two different sources are reported herein. Among of them, the methanolic extract of Amomum xanthioides showed significant inhibitory activity against a-glucosidase, the sucrase and maltase from rat intestine with IC50 value 3.10 4.20 and a glucosidase from baker’s yeast with IC50 values of 26.6 which is 25 times greater than the standard anti diabetic drug, acarbose. The preliminary observation provides the basis for further examination of Thai medicinal plants as supplement food and DM drug toward the treatment and prevention of diabetes. Keywords: a-Glucosidase inhibitor, Traditional Thai Medicinal Plant, non-communicable disease, hyperglycemia, Diabates Melitus, Amomum xanthioides *Corresponding author: E-mail: rwimon@aru.ac.th